Teacher's Efforts in Developing Student Morals in the Age New Normal (Upaya Guru dalam Pembinaan Akhlak Siswa di Masa New Normal) - Muliyani Muliyani; Usman Usman; Arsam Arsam (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
This study aims to identify and describe 1) Teacher's efforts in fostering the morals of Muhammadiyah Kendari High School students, especially during the Covid-19 pandemic and 2) Factors influencing the implementation of Kendari Muhammadiyah High School students' moral development, especially during the Covid-19 pandemic. This research is a type of qualitative research with a descriptive approach. Data analysis was carried out by analyzing the data obtained from interviews, field notes and other materials systematically so that they were easy to understand and inform others. The results of the study show that 1. The teacher's efforts in fostering the morals of SMA Muhammadiyah Kendari students, especially during the Covid-19 pandemic, are a) habituation. b) the example of the teacher. and c) giving advice, and. 2. Factors influencing the implementation of moral development for Muhammadiyah Kendari High School students, especially during the Covid-19 pandemic, namely a) Internal factors consisting of 1) heredity. and 2) the student's self-awareness factor. and, b) External factors, namely 1) family environment, 2) Educational environment, and 3) Community environment.Keywords: Moral Development, Teacher Efforts